Keputusan Pembelian dalam E- Commerce Shopee di Kecamatan Gunungpati Semarang - Heru Eko Prasetyo (Serat Acitya, 2021)
The purpose of this study was to determine the role of web site quality, security and online shopping confidence in purchasing decisions on shopee e-commerce in Gunung Pati District, Semarang. This study obtained data through questionnaires. The population in this study were users of shopee e- commerce sites in Gunung Pati District, Semarang. The sampling technique used was purposive sampling method with criteria for men and women aged 17 to 36 years in Gunung Pati Semarang District who had used and shop online at Shopee E-Commerce. Sample total was 100 respondents. The results of this study indicated that: (1) The quality of the website has a positive and significant effect on purchasing decisions, (2) Security has a positive and significant effect on purchasing decisions, (3) Trust has a positive and significant effect on purchasing decisions,